(untitled) (International Journal of Medical and Surgical Sciences, 2016)
One of the goals of hemodialysis is to maintain normal hydration status in ESRD patients. Pre hemodialysis systolic blood pressure is usually used as a clinical parameter of hydration status and to set ultrafiltration rate before Hd. It is unclear how much pre-Hd SBP correlated with hydration status. The aim was to determine correlation between pre-Hd SBP and hydration status before Hd. An observational correlation study was performed in two dialysis centers in Santiago, Chile, from January-June, 2011. Adult patients in Hd for at least three months, who gave their informed consent were included. Patients with pacemaker, amputee, hospitalized and metallic prostheses were excluded. Total-body water and overhydrated were assessed with bioimpedance spectroscopy before the first and third dialysis session of the week. Pre-Hd SBP, pre-Hd body weight, pre-Hd TBW and pre-Hd OH, were analyzed using Pearson correlation and linear regression model. 96 measurements were assessed, 52 % were male with median age 59.5 years. The correlation between pre-Hd SBP and pre-Hd overhydration was r=0.33, and total body water r=0.15, with a predicted value, R2=0.10 and R2 =0.14 respectively. Pre-Hd SBP had low correlation with pre-Hd hydration status and by itself, is not a reliable parameter to set ultrafiltration rate before Hd. Nevertheless Pre-Hd body weight predicted in 70 % the pre-Hd TBW.